Double transition metal-containing M2TiAlC2 o-MAX phases as Li-ion batteries anodes: a theoretical screening - Peng Xiao (Taylor & Francis Group, 2021)
Here, thermodynamic stability and lithium storage properties of double transition metal M2TiAlC2 o-MAX phases (M = Cr, V, Mo, Nb, Ta, Hf, Zr, Sc, Y, La) are theoretically investigated by density functional theory (DFT) calculation. M2TiAlC2 with a larger M atomic radius shows larger interlayer space that may benefit the Li-ion intercalation. A promising theoretical capacity of 276.87 mAh g-1 is predicted for Sc2TiAlC2. The low Li-ion diffusion barriers (0.57–0.64 eV) for M2TiAlC2 indicate the possibility to achieve fast Li-ion diffusion that is crucial for designing high-power batteries. This work provides opportunities to explore MAX phases as promising Li-ion storage materials.